Analisis Pemenuhan Gizi Terhadap Perkembangan Otak Anak Pada Usia Sekolah - I Ketut Mahardika; Alicia Dewi Nazarina; Fitriatul Aulia Rahma; Sofiatul Mukarromah; Firdha Yusmar; Riska Elan Fadila (Peneliti.net, 2022)
The purpose of this journal is to find out how the effect of nutritional fulfillment in children on brain growth during school. This journal uses qualitative research methods in the form of data collection through related journals. Fulfillment of nutrition for children is very important because childhood is also known as the golden period, which is a period where children's growth develops very rapidly. This period really needs attention because this period determines about 50% - 69% of the thinking ability in adult humans. This growth includes various aspects ranging from quantitative aspects or those that can be expressed in numbers to qualitative aspects or aspects that cannot be expressed in numbers. The development and growth of children is included in the qualitative aspect because it cannot be expressed in numbers. The ability to think, the level of maturity, and changes in character are included in the qualitative aspect during development. Parents or guardians need to pay special attention to children at this time so that children can grow and develop into superior individuals or individuals in the future.